TYPES OF SCIENCE AND THE OBLIGATION OF MUSLIM COMMUNITIES TO STUDY IT - meirison meirison; kasmidin kasmidin (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
This paper aims to describe the position and position of Science in Islam, which is divided into Sharia and Life Sciences, both of which are Fard Ain and Fardu Kifayah following the conditions faced by Muslims. In the hadiths of the Quran and the Hadith, it is found that Allah elevates the degree of knowledgeable people. The two types of Sharia and Life Sciences should work together for the benefit of Muslims. By conducting literature studies and descriptive approaches, it is found that Muslims who are consistent with Islamic teachings have succeeded in synergizing Islamic knowledge of Sharia and Life. Muslims were producing many discoveries of ijtihad results in various fields in the fields of Sharia and life sciences. This makes the Muslim Ummah stand amid other people with great dignity. This can be realized by creating a public tendency towards science, in other words, by creating a scientific revolution that starts from awareness in implementing Islamic law as a whole. This will make politicians who have only thought of eating and drinking turn into proponents of Muslims and science's benefit to get more votes for their victories by increasing the Education budget for the development of science